2005
DOI: 10.2188/jea.15.163
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Reproductive Tract Infections among Pregnant Women in Ten Communes in Nghe An Province, Vietnam

Abstract: The World Health Organization (WHO) estimated that 340 million new cases of trichomoniasis, gonorrhea, syphilis and chlamydia occurred globally in 1999 in men and women between the age of 15 to 49 years.1 The largest number of new infections occurred in South and Southeast Asia. Vietnamese health care workers believe the prevalence of a reproductive tract infection (RTI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
6
14
0
Order By: Relevance
“…The overall prevalence of trichomoniasis diagnosed by microscopic examination was 6.6%, with significant differences between asymptomatic and symptomatic women (0.7% and 19.3%, respectively). Data obtained on the asymptomatic group are consistent with results described in previous works in Vietnam [14,15]. In these studies, in fact, women were enrolled based only on their status of pregnancy or marriage not mentioning vaginal symptoms, and therefore might have been considered asymptomatic.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall prevalence of trichomoniasis diagnosed by microscopic examination was 6.6%, with significant differences between asymptomatic and symptomatic women (0.7% and 19.3%, respectively). Data obtained on the asymptomatic group are consistent with results described in previous works in Vietnam [14,15]. In these studies, in fact, women were enrolled based only on their status of pregnancy or marriage not mentioning vaginal symptoms, and therefore might have been considered asymptomatic.…”
Section: Discussionsupporting
confidence: 88%
“…Lan et al [14] showed that the prevalence of Trichomonas vaginalis infection in a group of married women in the Bavi district of North Vietnam was 1%. Similar results were obtained in a group of pregnant women in Hanoi, Vietnam [15]. As expected, prevalence was higher in women at high risk for sexually transmitted infection, as shown in a group of female sex workers in South Vietnam, showing a prevalence of 8.9% [16].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Yet research on coinfections during pregnancy and lactation has primarily focused on the associations of HIV and malaria with other pathogens including intestinal nematodes [18][19][20] or associations with other infections of the intestine 21 or the reproductive tract. [22][23][24] For example, intestinal nematode infections are often positively associated with one another 25 and BV is often positively associated with other common vaginal pathogens. [26][27][28] Much less is understood about interactions among vaginal, intestinal, urinary tract, skin, and oral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Induced abortion may increase the risk of reproductive tract infection (RTI), and the risk was also increased with the number of induced abortion. [18][19][20] …”
Section: Discussionmentioning
confidence: 99%